Investigation of magnetron injection locking and cascaded locking by solid-state microwave power source. Issue 3 (3rd July 2019) - Fu, Wenjie; Yan, Yang; Li, Xiaoyun
Abstract: The investigation of injection locking of cooker magnetron by a solid-state microwave power source is reported. Experimental results show that a 2.45 GHz cooker magnetron can be locked in continuous wave operation. In the frequency-locking bandwidth, the magnetron output frequency can be tuned by adjusting the injection source. The maximum frequency-locking bandwidth of 12 MHz and noise of less than −60 dBc at a 10 kHz offset frequency are observed. Cascaded locking of multiple magnetrons is also reported. The cascaded magnetrons show the same spectrum characteristics as the solid-state microwave power source and good phase stability, which leads to high efficiency in a power combining experiment.